Synthesis of novel derivatives of a versatile synthon : 4-amino-3-cyanopyrazole - Rodrigues, Lígia M. (2004)
Diazotisation of substituted arylamines followed by reaction with malononitrile gave substituted arylazomalononitriles. Cyclisation of these intermediates with two carbon sources and base gave the corresponding new 4-amino-3-cyanopyrazoles, in moderate yields. In one case the corresponding oxo-pyrazolopyrimidine was prepared.